The Relationship Between Personal Hygiene and Economic Level on The Incidence of Scabies in Nur El Haq Modern Islamic Boarding School Students - Yusuf, Andini; Hadi, Santriani; Murfat, Zulfitriani; Syamsu, Rachmat Faisal; Makmun, Armanto (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
The study, entitled